Evaluation of long-term therapy in cats with feline asthma and chronic bronchitis - Grotheer, Maike; Hirschberger, Johannes; Palić, Jelena; Hartmann, Katrin; Castelletti, Noemi; Schulz, Bianka (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
Objective Feline asthma (FA) and chronic bronchitis (CB) are common inflammatory diseases of the bronchial tree in cats. Even though both conditions are characterized by infiltration with different types of inflammatory cells, therapeutic measures are often similar. Little is known about potential differences in therapeutic management of these 2 airway diseases. Therefore, aim of the study was to compare initial and long-term treatment, therapeutic success, side effects, and owner satisfaction between cat with FA and those with CB.Material and methods Thirty-five cats with FA and 11 cats with CB were included in the retrospective cross-sectional study. Inclusion criteria were compatible clinical and radiographic signs and cytological evidence of eosinophilic inflammation (FA) or sterile neutrophilic inflammation (CB) in bronchoalveolar-lavage fluid (BALF). Cats with CB were excluded if evidence of pathological bacteria was present. Owners were contacted to fill out a standardized questionnaire on therapeutic management and response to treatment.Results Comparing treatment in both groups, no statistical significance was detected. Most cats were initially treated with corticosteroids as oral (FA 63%/CB 64%, P=1), inhaled (FA 34%/CB 55%, P=0.296) or injected formulations (FA 20%/CB 0%, P=0.171). In addition, oral bronchodilators (FA 43%/CB 45%, P=1), and antibiotics were given in some cases (FA 20%/CB 27%, P=0.682). For long-term management, 43% of cats with FA and 36% of cats with CB received inhaled corticosteroids (P=1), oral corticosteroids (FA 17%/CB 36%, P=0.220), and oral bronchodilators (FA 6%/CB 27%, P=0.084) as well as courses of antibiotics (FA 6%/CB 18%, P=0.238). Treatment-related side effects (polyuria/polydipsia, facial fungal infection, and diabetes mellitus) were reported in 4 cats with FA and 2 cats with CB. The majority of owners stated to be extremely or very satisfied with the response to treatment (FA 57%/CB 64%, P=1).Conclusion Significant differences regarding management and response to therapy for both diseases could not be detected.Clinical relevance Based on owner survey, chronic bronchial diseases as feline asthma and chronic bronchitis could be managed successfully with similar treatment.
Keywords: Feline bronchial disease; respiratory distress; cough; corticosteroids; bronchodilator